Shear wave elastography investigation of multifidus stiffness in individuals with low back pain. (August 2019) - Murillo, Carlos; Falla, Deborah; Rushton, Alison; Sanderson, Andy; Heneghan, Nicola R.
Abstract: The purpose of this study was to investigate differences in passive muscular stiffness between the superficial multifidus (SM) and deep multifidus (DM), and to compare their passive and active stiffness in individuals with low back pain (LBP) and asymptomatic individuals. Fifteen LBP individuals and 15 asymptomatic individuals were recruited. Passive stiffness of the SM and DM was measured bilaterally using shear wave elastography (SWE) with participants lying prone. Active stiffness was measured for the SM during trunk extension, and the contraction ratio was calculated. DM displayed higher passive muscular stiffness than SM in both the asymptomatic and LBP groups (14.41 ± 2.62 and 15.40 ± 2.77 kPa respectively; p < 0.001). Individuals with LBP exhibited higher passive muscular stiffness of SM (LBP: 10.15 ± 4.21, asymptomatic: 6.84 ± 1.69 kPa; p < 0.005) and a lower contraction ratio (LBP: 1.54 ± 0.47, asymptomatic: 2.65 ± 1.36 kPa; p < 0.003) compared to the asymptomatic group. The findings support a differentiation in passive muscular stiffness between SM and DM and provide evidence for an alteration in muscular stiffness at rest in individuals with LBP. The lower increase of muscular stiffness with contraction observed for those with LBP may reflect a deficit in activation of the multifidus.